2015
DOI: 10.5367/te.2015.0531
|View full text |Cite
|
Sign up to set email alerts
|

The influence of recent hotel amenities and green practices on guests’ price premium and revisit intention

Abstract: This study examines the influence of hotels' green practices, recent amenities, and traditionally salient attributes on customers' overall online evaluation, revisit intention and hotel performance. The researchers acquired data from more than one hundred US hotels located across different states with the assistance of an international hotel chain. In order to demonstrate the incremental information content of recently-adopted hotel amenities and levels of green initiatives, the study compared two extended mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 57 publications
7
45
1
2
Order By: Relevance
“…Our assertion is that employees are not in a position to force hotels to go green; however, the consumers/tourists/guests (i.e., these terms have been used interchangeably in tourism literature as they consume tourism product) [73][74][75][76][77] (just to name a few), can force the hotels to go green, otherwise they will not patronize those hotels that are not practicing sustainability [45,55,78].…”
Section: Green Consumers/touristsmentioning
confidence: 99%
“…Our assertion is that employees are not in a position to force hotels to go green; however, the consumers/tourists/guests (i.e., these terms have been used interchangeably in tourism literature as they consume tourism product) [73][74][75][76][77] (just to name a few), can force the hotels to go green, otherwise they will not patronize those hotels that are not practicing sustainability [45,55,78].…”
Section: Green Consumers/touristsmentioning
confidence: 99%
“…Environmental management is a broad term, covering issues such as environmental impact (aesthetic, cultural, ecological and social), sustainability, resource management and pollution [24]. Meanwhile, environmental management practices are important elements in an environmental management system, used to reduce the impact caused by an organisation onto the environment and make the operations more sustainable [25,26] while also increasing the number of environmental pro-active customer [27]. Additionally, green initiatives through green image, energy and resource management is believed to be able to give benefit to the hotel industry [28].…”
Section: Green Practices and Green Imagementioning
confidence: 99%
“…This paper puts forth customer satisfaction and customer loyalty as the consequence of environmental management practices and green image. There has been much research from many various fields that explored and investigated customer satisfaction and customer loyalty, but there is still limited research focusing on green and environmental issues [27,48], especially in Malaysia. Furthermore, there is paucity in research conducted on environmental management practices in hotel organisations [14,26,16,31] that influence customer satisfaction [23,49] and hotel guests' attitudes [50].…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…The competition between tourist destinations is affected by the quality offered by hotels in the region, and for this reason, to add value to the hotel and to the region is necessary to provide quality services and to pay attention to the customer needs and customer satisfaction [26]. The study of [27] indicated that the availability of recently-added amenities and green practice initiatives, have a positive influence on customers' overall ratings and hotel performance. Also, [28] found that green practices were positively related to guest satisfaction and return intentions.…”
Section: Resultsmentioning
confidence: 99%